THE ROLE OF SIRAA VYADHANA IN TREATING BHASMAKA ROGA (ATYAGNI) - Puripanda, *S.Kamalakar; Renuka, M; Vaidya, S M. (International Journal of Ayurveda and Pharma Research, 2016)
Acharya Charaka in Grahani Chikitsa Adhyaya explained about Siraa Vyadhana in the management of Atyagni. Atyagni can be considered as one of the serious conditions as it leads to severe weakness thereby patient may succumb to death also. Strength of the patient, nature and Seriousness of the disease should be considered before performing Siraa Vyadhana. Agni is a key factor in transformation of consumed Ahara Dravya of Vijatiya origin to Sajatiya nature with the help of Vata, converts the Ahara into Rasadi Dhatus and Malas. In this disorder mainly Vata and Agni plays major role. Because of this Anilaanalam the food is digested very quickly it leads to effect on Dhatwagni and Uttharothara Dhatu Prakriya. â€œDepletion of digestive fireâ€ which is being developed after Siraa Vyadhana. Acharyas clearly explained about Raktha, Pitta and Agni relation in different concepts, if draw the Raktha from body directly it acts on Raktha Dhatu after that Rasa Dhatu, Dhatwagni Mandhya and Mandhata of Agni. So in Atyagni condition Siraa Vyadhana is one of the treatment modality. Intension of this paper is to highlight the concept and effect of Siraa Vyadhana in Atyagni (Bhasmaka Roga).